Porous core-shell type magnetic composite microsphere as well as preparation method and application thereof
The preparation of porous core-shell magnetic composite microspheres with grafted polymer brushes and functional groups addresses the limitations of existing methods, resulting in monodisperse microspheres with enhanced magnetic responsiveness and multifunctionality for various biotechnical applications.
Patent Information
- Application Number
- CN202411535707.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-20
AI Technical Summary
Existing methods for preparing magnetic polymer composite microspheres face issues such as wide particle size distribution, irregular shapes, inconsistent magnetic content, and difficulty in removing excess Fe3O4, leading to uneven polymer surfaces and agglomeration, which limits their application in areas like immobilized enzymes, cell separation, and drug carriers.
A method involving the preparation of porous core-shell magnetic composite microspheres using Fe3O4@SiO2 nanoparticles, modified with aminopropyltriethoxysilane, followed by atom transfer radical polymerization to graft polymer brushes, and subsequent reverse suspension polymerization to form a polymer shell, with L-cysteine modification to introduce -SH, -NH2, and -COOH groups, enhancing compatibility and functionality.
The method produces monodisperse magnetic composite microspheres with high magnetization intensity and multifunctional groups, improving magnetic responsiveness and enabling applications in cross-linking encapsulation of enzymes, heavy metal ion adsorption, protein purification, and drug carriers.
Smart Images

Figure CN119158508A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic polymer microspheres, and in particular to porous core-shell magnetic composite microspheres and a preparation method and application thereof. Background Art
[0002] Magnetic polymer composite microspheres not only have good biocompatibility and chemical stability of polymer microspheres, but also have good paramagnetism. They can not only make polymer materials have chemically active functional groups (such as -COOH, -NH2, -OH, -SH, -CHO, etc.) through copolymerization or modification, but also make them have guiding ability under the action of an external magnetic field. Magnetic composite microspheres have been widely used in immobilized enzymes, cell separation, protein purification, drug carriers, metal ion adsorption, etc.
[0003] The preparation methods of magnetic polymer composite microspheres mainly include embedding method, in-situ growth method and monomer polymerization method. The embedding method is to combine with polymer through intermolecular forces, hydrogen bonds, chelation or covalent bonds, and prepare polymer microspheres by means of atomization, flocculation, deposition, evaporation, etc. This method is simple to operate, but the microspheres have a wide particle size distribution, irregular shapes, inconsistent magnetic content, and impurities in the shell layer, which limits their application.
[0004] The in-situ growth method uses the functional groups on the surface of polymer microspheres to chemically bond with iron ions, and then increases the pH value and temperature to obtain magnetic polymer microspheres containing Fe3O4. The magnetic composite microspheres prepared by this method have strong magnetism, a magnetic content of more than 30%, uniform particle size distribution, and good monodispersity. However, additional Fe3O4 will be generated on the surface of the microspheres and in the solution, resulting in an uneven polymer surface and difficulty in removing excess Fe3O4. There are many factors that affect the in-situ generation of magnetic microspheres. The surface of the polymer microspheres must contain specific functional groups and the synthesis conditions must be strictly controlled to obtain the desired magnetic composite microspheres.
[0005] Monomer polymerization methods include suspension polymerization, emulsion polymerization, dispersion polymerization, free radical polymerization, etc. Since the prepared products have the advantages of small particle size, good dispersibility, and easy functionalization, the method of preparing magnetic polymer microspheres by graft polymerization on the surface of magnetic particles is currently the most widely used. Among them, suspension polymerization has the advantages of easy control of reaction system temperature, diffusion of reaction heat, and low cost. The particle size of magnetic polymer microspheres prepared by inverse suspension polymerization is uniform, and the size of the microsphere particle size can be controlled by changing the reaction conditions, thereby preparing magnetic polymer composite microspheres with high magnetic content and functionalization.
[0006] The key to the monomer polymerization method is that the organic monomers on the surface of the magnetic particles can smoothly undergo polymerization reactions. Some monomers in the polymerization reaction are hydrophobic substances, which are not easy to connect with the hydrophilic groups on the surface of the magnetic particles. Therefore, it is necessary to first modify the surface of the magnetic particles to make them hydrophobic, or adjust the organic phase composition in the polymerization reaction, and then the polymerization reaction can continue. Patent CN106861570A discloses a method for preparing magnetic core-shell microspheres with thermosensitive properties and its application in cellulase immobilization. First, Fe3O4@SiO2 is synthesized, then modified with methacryloxypropyltrimethoxysilane, and then monomers GMA and NIPAM are added to react to obtain thermosensitive magnetic composite microspheres. The microspheres are applied to immobilized cellulase. At high temperatures, the thermosensitive polymers on the surface of the microspheres become hydrophobic and wrap the enzyme molecules, and at low temperatures, they become hydrophilic and release the enzyme, thereby improving the enzyme activity recovery ability and thermal stability.
[0007] Fe3O4 has the characteristics of high specific surface area, low toxicity, and good biocompatibility. It is the main coating material of magnetic polymer composite microspheres today. The key to preparing magnetic polymer microspheres is how to form a polymer shell on the surface of inorganic magnetic particles. The high specific surface area makes Fe3O4 nanoparticles have high surface energy and are prone to agglomeration. However, surface modification can improve the monodispersity of nanoparticles and improve their stability. The surface of magnetic nanoparticles can be modified by oleic acid and silane coupling agents. Oleic acid modification can prevent agglomeration, but there are problems such as the compatibility of surfactants and carrier liquids and the limitations of the carrier liquid itself during magnetic dispersion. The preparation method of silicon dioxide is simple, stable, non-toxic, and biocompatible. Coating Fe3O4 with silicon dioxide can protect the magnetic core and prevent Fe3O4 from directly contacting other substances on the surface of silicon dioxide. The magnetic nanoparticles coated with silicon dioxide have the advantages of being stable in aqueous solution (at a lower pH), easy surface modification, and good monodispersity.
[0008] The surface of Fe3O4@SiO2 nanoparticles contains hydroxyl functional groups, which show hydrophilicity, making it easier to graft functional groups on the surface. Atom transfer radical polymerization uses the hydroxyl reaction points on the surface of magnetic particles to first introduce active free radicals or organic halide initiators on the surface of magnetic particles to make them the initiation center. In the presence of transition metal halide complexes, polymer monomers are initiated to undergo polymerization reactions on the surface of magnetic particles to prepare polymer brushes. Atom transfer radical polymerization has the advantages of controllable molecular weight, narrow molecular weight distribution, small particle size, easy modification of polymer end groups, and strong molecular design capabilities.
[0009] Although Fe3O4 coated with SiO2 can protect the magnetic core and prevent Fe3O4 from direct contact with other substances on the surface of silica, silica coating also has its own disadvantages, such as not being able to exist stably under alkaline conditions, forming pores on the surface of amorphous SiO2, causing oxygen or other small molecules to diffuse into the nanoparticles and react with them. The poor compatibility of inorganic and organic materials will lead to uneven dispersion of inorganic materials in organic materials, and agglomeration is prone to occur. Summary of the invention
[0010] In order to solve the above problems, the present invention provides a porous core-shell magnetic composite microsphere and a preparation method and application thereof. The porous core-shell magnetic composite microsphere prepared by the preparation method provided by the present invention has good sphericity, monodispersity and contains multifunctional groups on the surface, so that the magnetic composite microsphere can be used for cross-linking encapsulation of immobilized enzymes, adsorption of heavy metal ions, drug carriers and other aspects.
[0011] In order to achieve the above object, the present invention provides the following technical solutions:
[0012] The present invention provides a method for preparing porous core-shell magnetic composite microspheres, comprising the following steps:
[0013] 1) Fe3O4@SiO2, anhydrous ethanol and 3-aminopropyltriethoxysilane were mixed and reacted at 60°C to obtain Fe3O4@SiO2-NH2;
[0014] 2) mixing the Fe3O4@SiO2-NH2 obtained in step 1) with toluene, triethylamine and 2-bromoisobutyl bromide, and reacting at 20° C. to obtain Fe3O4@SiO2-Br;
[0015] 3) mixing the Fe3O4@SiO2-Br obtained in step 2) with monomer, N,N-dimethylformamide, copper bromide and 2'2-bipyridine, and reacting them under nitrogen protection at 90° C. to obtain Fe3O4@SiO2-P(GMA-HEMA);
[0016] 4) mixing the Fe3O4@SiO2-P(GMA-HEMA) obtained in step 3) with monomers, 1-vinyl-2-pyrrolidone, ethylene glycol dimethacrylate, azobisisobutyronitrile, cyclohexanol, sorbitan monooleate, tetrachloroethylene, and n-heptane, and performing polymerization reaction under nitrogen protection at 55° C. to obtain Fe3O4@SiO2 / P(GMA-HEMA-NVP);
[0017] 5) mixing the Fe3O4@SiO2 / P(GMA-HEMA-NVP) obtained in step 4) with L-cysteine, azobisisobutyronitrile and anhydrous ethanol, reacting the mixture under nitrogen protection at 65°C, and washing and drying the mixture in sequence to obtain porous core-shell magnetic composite microspheres;
[0018] The monomers in step 3) or 4) include one or more of glycidyl methacrylate, hydroxyethyl methacrylate, styrene and methacrylic acid.
[0019] Preferably, in step 1), the mass ratio of Fe3O4@SiO2, the volume of anhydrous ethanol and 3-aminopropyltriethoxysilane is 0.1 g:150 mL:1.2 g;
[0020] The reaction time is 12 h.
[0021] Preferably, in step 2), the ratio of the mass of Fe3O4@SiO2-NH2 to the volume of toluene, the volume of triethylamine, and the volume of 2-bromoisobutyl bromide is 0.1 g: 20 mL: 5 mL: 2 mL;
[0022] The reaction time is 24h.
[0023] Preferably, the mass ratio of the Fe3O4@SiO2-Br obtained in step 3) to the volume of the monomer, the volume of N,N-dimethylformamide, the mass of copper bromide, and the mass ratio of bipyridine is 0.1 g: 3 mL: 7 mL: 25 mg: 56 mg;
[0024] The reaction time is 24h.
[0025] Preferably, in the step 4), the mass ratio of Fe3O4@SiO2-P(GMA-HEMA) to the mass of the monomer, the mass of 1-vinyl-2-pyrrolidone, the mass of ethylene glycol dimethacrylate, the mass of azobisisobutyronitrile, the mass of cyclohexanol, the mass of sorbitan monooleate, the volume of tetrachloroethylene, and the volume ratio of n-heptane is 0.5g:5.5g:1.1g:2.1g:0.2g:1.9-7.8g:1g:35mL:109mL;
[0026] The polymerization reaction time is 5 h.
[0027] Preferably, in step 5), the mass ratio of Fe3O4@SiO2 / P(GMA-HEMA-NVP) to the mass of L-cysteine, the mass of azobisisobutyronitrile, and the volume ratio of anhydrous ethanol is 0.1 g:1.5 g:50 mg:100 mL;
[0028] The reaction time is 6 h.
[0029] Preferably, when the monomers in step 3) are glycidyl methacrylate and hydroxyethyl methacrylate, the volume ratio of glycidyl methacrylate to hydroxyethyl methacrylate is 2:1;
[0030] When the monomers in step 4) are glycidyl methacrylate and hydroxyethyl methacrylate, the mass ratio of glycidyl methacrylate to hydroxyethyl methacrylate is 4.3:2.2.
[0031] Preferably, when the monomers in step 3) are styrene and methacrylic acid, the volume ratio of styrene to methacrylic acid is 2:1;
[0032] When the monomers in step 4) are styrene and methacrylic acid, the mass ratio of styrene to methacrylic acid is 4.3:2.2.
[0033] The present invention also provides a porous core-shell magnetic composite microsphere prepared by the preparation method described in the above technical solution.
[0034] The present invention also provides the use of the porous core-shell magnetic composite microspheres described in the above technical solution in any one of cross-linking and encapsulating immobilized enzymes, heavy metal ion adsorption, protein purification, cell separation and drug carriers.
[0035] The invention adopts a reverse microemulsion method to prepare Fe3O4@SiO2 magnetic nanoparticles (prepared according to the document DING HL, ZHANG YX, WANG S, et al. Fe3O4@SiO2 Core / Shell Nanoparticles: The Silica Coating Regulations with a Single Core for Different Core Sizes and Shell Thicknesses [J]. Chemistry of Materials, 2012, 24 (23): 4572-80.), adopts an atom transfer radical polymerization method to graft a polymer brush on the surface of Fe3O4@SiO2 to change the compatibility of the magnetic nanoparticles with a monomer, and then adopts a reverse suspension polymerization technology to prepare core-shell magnetic composite microspheres with Fe3O4@SiO2 nanoparticles grafted with a polymer brush as a core and different polymers as a shell, and adopts L-cysteine to modify the composite microspheres to obtain multifunctional core-shell magnetic composite microspheres containing -SH, -NH2 and -COOH active groups. The magnetic composite microspheres can be used to adsorb heavy metal ions and react with crosslinking agents to crosslink and encapsulate immobilized enzymes. Since methacrylate materials can improve the biocompatibility of drug carrier polymers and reduce toxic side effects, if the monomer is methacrylate, the magnetic composite microspheres can also be used as drug carriers.
[0036] Beneficial effects of the present invention:
[0037] 1. By grafting polymer brushes on the surface of magnetic nanoparticles, not only the compatibility of magnetic nanoparticles and monomers is improved, but also the contact between Fe3O4 and other substances is minimized. The resulting composite microspheres have a higher magnetization intensity, which is beneficial to improve the magnetic responsiveness of the composite material ( Figure 2 ).
[0038] 2. Monodisperse magnetic composite microspheres can be obtained by coating Fe3O4 with SiO2 and grafting polymer brushes. Different types of magnetic composite microspheres can also be prepared by grafting different types of polymer brushes according to production requirements.
[0039] 3. The magnetic composite microspheres were modified with L-cysteine to obtain active groups containing -SH, -NH2, and -COOH ( Figure 3 )'s multifunctional core-shell magnetic composite microspheres can be used for cross-linking and encapsulating immobilized enzymes, adsorption of heavy metal ions, protein purification, cell separation, and drug carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0041] Figure 1 TEM image and particle size distribution diagram of Fe3O4@SiO2 in Example 1;
[0042] Figure 2 is the room temperature magnetization curve of Fe3O4@SiO2 / P(GMA-HEMA-NVP) magnetic composite microspheres in Example 1;
[0043] Figure 3 The infrared spectra of different magnetic composite microspheres in Example 1, (1) is Fe3O4@SiO2-NH2, (2) is Fe3O4@SiO2 / P(GMA-HEMA-NVP), and (3) is L-cysteine functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP);
[0044] Figure 4 N2 adsorption-desorption curves of magnetic composite microspheres with different porogen dosages in Examples 1-4, a corresponds to Example 4, b corresponds to Example 3, c corresponds to Example 1, and d corresponds to Example 2;
[0045] Figure 5 The removal rate of Cu(Ⅱ) by magnetic microspheres with different functionalizations. DETAILED DESCRIPTION
[0046] The present invention provides a method for preparing porous core-shell magnetic composite microspheres, comprising the following steps:
[0047] 1) Fe3O4@SiO2, anhydrous ethanol and 3-aminopropyltriethoxysilane were mixed and reacted at 60°C to obtain Fe3O4@SiO2-NH2;
[0048] 2) mixing the Fe3O4@SiO2-NH2 obtained in step 1) with toluene, triethylamine and 2-bromoisobutyl bromide, and reacting at 20° C. to obtain Fe3O4@SiO2-Br;
[0049] 3) mixing the Fe3O4@SiO2-Br obtained in step 2) with monomer, N,N-dimethylformamide, copper bromide and 2'2-bipyridine, and reacting them under nitrogen protection at 90° C. to obtain Fe3O4@SiO2-P(GMA-HEMA);
[0050] 4) mixing the Fe3O4@SiO2-P(GMA-HEMA) obtained in step 3) with monomers, 1-vinyl-2-pyrrolidone, ethylene glycol dimethacrylate, azobisisobutyronitrile, cyclohexanol, sorbitan monooleate, tetrachloroethylene, and n-heptane, and performing polymerization reaction under nitrogen protection at 55° C. to obtain Fe3O4@SiO2 / P(GMA-HEMA-NVP);
[0051] 5) mixing the Fe3O4@SiO2 / P(GMA-HEMA-NVP) obtained in step 4) with L-cysteine, azobisisobutyronitrile and anhydrous ethanol, reacting the mixture under nitrogen protection at 65°C, and washing and drying the mixture in sequence to obtain porous core-shell magnetic composite microspheres;
[0052] The monomers in step 3) or 4) include one or more of glycidyl methacrylate, hydroxyethyl methacrylate, styrene and methacrylic acid.
[0053] The present invention mixes Fe3O4@SiO2, anhydrous ethanol and 3-aminopropyltriethoxysilane, and reacts them at 60°C to obtain Fe3O4@SiO2-NH2.
[0054] The present invention has no special limitation on the source of the Fe3O4@SiO2, and it can be prepared by commercially available or conventional methods. In the present invention, the mass ratio of the Fe3O4@SiO2, the volume of anhydrous ethanol and the mass ratio of 3-aminopropyltriethoxysilane is preferably 0.1 g:150 mL:1.2 g; and the reaction time is preferably 12 h.
[0055] The present invention mixes the obtained Fe3O4@SiO2-NH2 with toluene, triethylamine and 2-bromoisobutyl bromide, and reacts at 20°C to obtain Fe3O4@SiO2-Br. In the present invention, the mass ratio of the Fe3O4@SiO2-NH2 to the volume of toluene, the volume of triethylamine and the volume of 2-bromoisobutyl bromide is preferably 0.1 g: 20 mL: 5 mL: 2 mL; and the reaction time is preferably 24 h.
[0056] The present invention mixes the obtained Fe3O4@SiO2-P(GMA-HEMA) with monomers, 1-vinyl-2-pyrrolidone, ethylene glycol dimethacrylate, azobisisobutyronitrile, cyclohexanol, sorbitan monooleate, tetrachloroethylene, and n-heptane, and performs polymerization reaction under nitrogen protection at 55°C to obtain Fe3O4@SiO2 / P(GMA-HEMA-NVP). In the present invention, the mass ratio of the Fe3O4@SiO2-Br to the volume of the monomer, the volume of N,N-dimethylformamide, the mass of copper bromide, and the mass ratio of bipyridine is preferably 0.1g:3mL:7mL:25mg:56mg; the reaction time is preferably 24h. In the present invention, the monomer includes one or more of glycidyl methacrylate, hydroxyethyl methacrylate, styrene, and methacrylic acid. In the present invention, when the monomers are preferably glycidyl methacrylate and hydroxyethyl methacrylate, the volume ratio of glycidyl methacrylate to hydroxyethyl methacrylate is preferably 2: 1. In the present invention, when the monomers are preferably styrene and methacrylic acid, the volume ratio of styrene to methacrylic acid is preferably 2: 1.
[0057] The present invention mixes the obtained Fe3O4@SiO2-P(GMA-HEMA) with monomers, 1-vinyl-2-pyrrolidone, ethylene glycol dimethacrylate, azobisisobutyronitrile, cyclohexanol, sorbitan monooleate, tetrachloroethylene, and n-heptane, and performs polymerization reaction under nitrogen protection at 55°C to obtain Fe3O4@SiO2 / P(GMA-HEMA-NVP). In the present invention, the mass ratio of the Fe3O4@SiO2-P(GMA-HEMA) to the mass of the monomers, the mass of 1-vinyl-2-pyrrolidone, the mass of ethylene glycol dimethacrylate, the mass of azobisisobutyronitrile, the mass of cyclohexanol, the mass of sorbitan monooleate, the volume of tetrachloroethylene, and the volume ratio of n-heptane is preferably 0.5g:5.5g:1.1g:2.1g:0.2g:1.9-7.8g:1g:35mL:109mL; and the time of the polymerization reaction is preferably 5h. In the present invention, when the monomers are preferably glycidyl methacrylate and hydroxyethyl methacrylate, the mass ratio of glycidyl methacrylate to hydroxyethyl methacrylate is preferably 4.3:2.2. In the present invention, when the monomers are preferably styrene and methacrylic acid, the mass ratio of styrene to methacrylic acid is preferably 4.3:2.2. In the present invention, the cyclohexanol is used as a porogen.
[0058] The method comprises mixing the obtained Fe3O4@SiO2 / P (GMA-HEMA-NVP) with L-cysteine, azobisisobutyronitrile and anhydrous ethanol, reacting the mixture under nitrogen protection at 65°C, and washing and drying the mixture in sequence to obtain porous core-shell magnetic composite microspheres.
[0059] In the present invention, the volume ratio of the mass of Fe3O4@SiO2 / P(GMA-HEMA-NVP) to the mass of L-cysteine, the mass of azobisisobutyronitrile, and anhydrous ethanol is preferably 0.1g:1.5g:50mg:100mL; and the reaction time is preferably 6h.
[0060] The present invention provides a porous core-shell magnetic composite microsphere prepared by the preparation method described in the above technical solution, the pore size is 10nm-70nm, and the groups contained are -SH, -NH2, and -COOH.
[0061] The present invention also provides the use of the porous core-shell magnetic composite microspheres described in the above technical solution in any one of cross-linking and encapsulating immobilized enzymes, heavy metal ion adsorption, protein purification, cell separation and drug carriers.
[0062] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0063] Example 1
[0064] (1) ATRP functionalization initiated on Fe3O4@SiO2 surface
[0065] Monodisperse SiO2-coated Fe3O4 magnetic nanoparticles were prepared by the reverse microemulsion method (prepared according to the literature DING HL, ZHANG YX, WANG S, et al. Fe3O4@SiO2Core / ShellNanoparticles: The Silica Coating Regulations with a Single Core for Different Core Sizes and Shell Thicknesses[J]. Chemistry of Materials, 2012, 24(23): 4572-80.).
[0066] 0.1 g of Fe3O4@SiO2 was dispersed in 150 mL of anhydrous ethanol, and 1.2 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise into the reaction system at 60 °C for 12 h to obtain Fe3O4@SiO2-NH2.
[0067] The above 0.1 g APTES-modified magnetic nanoparticles were dispersed in 10 mL toluene, 5 mL triethylamine was added, 2 mL 2-bromoisobutyl bromide was dissolved in 10 mL toluene at 0°C and added dropwise to the reaction system, reacted at 20°C for 24 h, washed and dried for later use, and Fe3O4@SiO2-Br was obtained.
[0068] 0.1g Fe3O4@SiO2-Br, 2mL glycidyl methacrylate (GMA), 1mL hydroxyethyl methacrylate (HEMA) were dispersed in 7mL N,N-dimethylformamide (DMF), and then 25mg copper bromide and 56mg 2'2-bipyridine were added. N2 was passed for 30 minutes, and then freeze-vacuum-fill N2 was cycled for 3 times, and finally heated to 90℃ under N2 protection and reacted for 24h to obtain magnetic nanoparticles of grafted polymer brushes, referred to as Fe3O4@SiO2-P (GMA-HEMA).
[0069] (2) Synthesis of magnetic composite microspheres
[0070] 0.5 g Fe3O4@SiO2-P(GMA-HEMA) was dispersed in a solution containing 4.3 g glycidyl methacrylate, 2.2 g hydroxyethyl methacrylate, 1.1 g 1-vinyl-2-pyrrolidone, 2.1 g ethylene glycol dimethacrylate (EDMA), 0.2 g azobisisobutyronitrile (AIBN), and 1.9 g cyclohexanol, and then added to a mixed solution consisting of 1 g sorbitan monooleate (Span80), 35 mL tetrachloroethylene, and 109 mL n-heptane, and reverse suspension polymerization was carried out at 55 °C under nitrogen protection for 5 h. After washing and drying, Fe3O4@SiO2 / P(GMA-HEMA-NVP) was obtained.
[0071] (3) Preparation of functionalized magnetic composite microspheres
[0072] 0.5g Fe3O4@SiO2 / P(GMA-HEMA-NVP), 1.5g L-cysteine, 50mg azobisisobutyronitrile (AIBN) were added to 100mL anhydrous ethanol, reacted at 65℃ for 6h under nitrogen protection, and the residue was washed with dichloromethane, methanol, water and methanol in sequence, and finally dried at 60℃ overnight to obtain functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP). The prepared functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) has a pore size of 10.5nm.
[0073] Example 2
[0074] The steps of Example 2 are the same as those of Example 1, except that the amount of cyclohexanol added is 3.9 g. The pore size of the prepared functionalized Fe3O4@SiO2 / P (GMA-HEMA-NVP) is 12.2 nm.
[0075] Example 3
[0076] The steps of Example 3 are the same as those of Example 1, except that the amount of cyclohexanol added is 5.8 g. The pore size of the prepared functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) is 15.6 nm.
[0077] Example 4
[0078] The steps of Example 4 are the same as those of Example 1, except that the amount of cyclohexanol added is 7.8 g. The pore size of the prepared functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) is 18.6 nm.
[0079] It can be seen from Examples 1-4 that as the amount of cyclohexanol added increases, the pore size of the obtained magnetic composite microspheres increases ( Figure 4), the pore size can be adjusted by the amount of porogen used. The larger the pore size, the smaller the comparative area, and the tendency for the adsorption amount to decrease.
[0080] Example 5
[0081] (1) ATRP functionalization initiated on Fe3O4@SiO2 surface
[0082] Monodisperse SiO2-coated Fe3O4 magnetic nanoparticles were prepared by inverse microemulsion method.
[0083] 0.1 g of Fe3O4@SiO2 was dispersed in 150 mL of anhydrous ethanol, and 1.2 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise into the reaction system at 60 °C for 12 h to obtain Fe3O4@SiO2-NH2.
[0084] The above 0.1 g APTES-modified magnetic nanoparticles were dispersed in 10 mL toluene, 5 mL triethylamine was added, 2 mL 2-bromoisobutyl bromide was dissolved in 10 mL toluene at 0°C and added dropwise to the reaction system, reacted at 20°C for 24 h, washed and dried for later use, and Fe3O4@SiO2-Br was obtained.
[0085] 0.1g Fe3O4@SiO2-Br, 2mL styrene, 1mL methacrylic acid were dispersed in 7mL DMF, and then 25mg copper bromide and 56mg 2'2-bipyridine were added. N2 was passed through for 30 minutes, and then freeze-vacuum-fill N2 was cycled for 3 times, and finally heated to 90℃ under N2 protection and reacted for 24h to obtain magnetic nanoparticles of grafted polymer brushes.
[0086] (2) Synthesis of magnetic composite microspheres
[0087] 0.5 g Fe3O4@SiO2-P(St-MMA) was dispersed in a solution containing 4.3 g styrene, 2.2 g methacrylic acid, 1.1 g 1-vinyl-2-pyrrolidone, 2.1 g divinylbenzene, 0.2 g azobisisobutyronitrile (AIBN), and 1.9 g cyclohexanol, and then added to a mixed solution consisting of 1 g sorbitan monooleate (Span 80), 35 mL tetrachloroethylene, and 109 mL n-heptane. Reverse suspension polymerization was carried out at 55 °C under nitrogen protection for 5 h, and Fe3O4@SiO2 / P(St-MMA-NVP) was obtained after washing and drying.
[0088] (3) Preparation of functionalized magnetic composite microspheres
[0089] 0.5 g Fe3O4@SiO2 / P (St-MMA-NVP), 1.5 g L-cysteine, and 50 mg azobisisobutyronitrile (AIBN) were added to 100 mL anhydrous ethanol, reacted at 65 °C for 6 h under nitrogen protection, and the residue was washed with dichloromethane, methanol, water and methanol in turn, and finally dried at 60 °C overnight to obtain functionalized Fe3O4@SiO2 / P (St-MMA-NVP).
[0090] Example 6
[0091] The functionalized Fe3O4@SiO2 / P (GMA-HEMA-NVP) with different pore sizes in Examples 1-4 was used to treat wastewater containing Cu(II). 100 mL of 100 mg / L CuSO4·5H2O solution was added to a 250 mL conical flask, the pH was adjusted to 5.0 with 0.1 mol / L HCl, and 0.75 g / L of magnetic nanoparticles was added. The solution was placed in a constant temperature oscillator at 25°C, and after adsorption for 2 hours, it was filtered with a 0.45 μm syringe filter. The remaining Cu(II) concentration of the solution was determined by an atomic absorption spectrophotometer. The experiment was repeated three times, and the average value was taken as the final result. When the pH value was 5.0 and the adsorption time was 2h, the removal efficiency of Cu(Ⅱ) by 18.6nm functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) was 81%, the removal efficiency of Cu(Ⅱ) by 15.6nm functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) was 85%, the removal efficiency of Cu(Ⅱ) by 12.2nm functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) was 88%, and the removal efficiency of Cu(Ⅱ) by 10.5nm functionalized Fe3O4@SiO2 / P(GMA-HEMA-NVP) was 91%.
[0092] Example 7
[0093] The functionalized Fe3O4@SiO2 / P (St-MMA-NVP) in Example 5 was used to treat wastewater containing Cu(Ⅱ). 100 mL of 100 mg / L CuSO4·5H2O solution was added to a 250 mL conical flask, the pH was adjusted to 5.0 with 0.1 mol / L HCl, and 0.75 g / L of magnetic nanoparticles were added. The solution was placed in a constant temperature oscillator at 25°C. After adsorption for 2 hours, the solution was filtered with a 0.45 μm syringe filter, and the remaining Cu(Ⅱ) concentration of the solution was determined by an atomic absorption spectrophotometer. The experiment was repeated three times, and the average value was taken as the final result. At a pH of 5.0, the removal rate of Cu(Ⅱ) by the magnetic composite microspheres after adsorption for 2 hours can reach 93%.
[0094] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing porous core-shell magnetic composite microspheres, characterized in that: The following steps are involved: 1) Fe3O4@SiO2, anhydrous ethanol and 3-aminopropyltriethoxysilane were mixed and reacted at 60°C to obtain Fe3O4@SiO2-NH2; 2) mixing the Fe3O4@SiO2-NH2 obtained in step 1) with toluene, triethylamine and 2-bromoisobutyl bromide, and reacting at 20° C. to obtain Fe3O4@SiO2-Br; 3) mixing the Fe3O4@SiO2-Br obtained in step 2) with monomer, N,N-dimethylformamide, copper bromide and 2'2-bipyridine, and reacting them under nitrogen protection at 90° C. to obtain Fe3O4@SiO2-P(GMA-HEMA); 4) mixing the Fe3O4@SiO2-P(GMA-HEMA) obtained in step 3) with monomers, 1-vinyl-2-pyrrolidone, ethylene glycol dimethacrylate, azobisisobutyronitrile, cyclohexanol, sorbitan monooleate, tetrachloroethylene, and n-heptane, and performing polymerization reaction under nitrogen protection at 55° C. to obtain Fe3O4@SiO2 / P(GMA-HEMA-NVP); 5) mixing the Fe3O4@SiO2 / P(GMA-HEMA-NVP) obtained in step 4) with L-cysteine, azobisisobutyronitrile and anhydrous ethanol, reacting the mixture under nitrogen protection at 65°C, and washing and drying the mixture in sequence to obtain porous core-shell magnetic composite microspheres; The monomers in step 3) or 4) include one or more of glycidyl methacrylate, hydroxyethyl methacrylate, styrene and methacrylic acid.
2. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of Fe3O4@SiO2, the volume of anhydrous ethanol and the mass ratio of 3-aminopropyltriethoxysilane is 0.1 g:150 mL:1.2 g; The reaction time is 12 h.
3. The preparation method according to claim 1, characterized in that: In the step 2), the ratio of the mass of Fe3O4@SiO2-NH2 to the volume of toluene, the volume of triethylamine, and the volume of 2-bromoisobutyl bromide is 0.1 g: 20 mL: 5 mL: 2 mL; The reaction time is 24h.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the Fe3O4@SiO2-Br obtained in step 3) to the volume of the monomer, the volume of N,N-dimethylformamide, the mass of copper bromide, and the mass ratio of bipyridine is 0.1 g: 3 mL: 7 mL: 25 mg: 56 mg; The reaction time is 24h.
5. The preparation method according to claim 1, characterized in that: In the step 4), the mass ratio of Fe3O4@SiO2-P(GMA-HEMA) to the mass of the monomer, the mass of 1-vinyl-2-pyrrolidone, the mass of ethylene glycol dimethacrylate, the mass of azobisisobutyronitrile, the mass of cyclohexanol, the mass of sorbitan monooleate, the volume of tetrachloroethylene, and the volume ratio of n-heptane is 0.5g:5.5g:1.1g:2.1g:0.2g:1.9-7.8g:1g:35mL:109mL; The polymerization reaction time is 5 h.
6. The preparation method according to claim 1, characterized in that: In the step 5), the volume ratio of the mass of Fe3O4@SiO2 / P(GMA-HEMA-NVP), the mass of L-cysteine, the mass of azobisisobutyronitrile, and the volume ratio of anhydrous ethanol is 0.1 g:1.5 g:50 mg:100 mL; The reaction time is 6 h.
7. The preparation method according to claim 1, characterized in that: When the monomers in step 3) are glycidyl methacrylate and hydroxyethyl methacrylate, the volume ratio of glycidyl methacrylate to hydroxyethyl methacrylate is 2:1; When the monomers in step 4) are glycidyl methacrylate and hydroxyethyl methacrylate, the mass ratio of glycidyl methacrylate to hydroxyethyl methacrylate is 4.3:2.
2.
8. The preparation method according to claim 1, characterized in that: When the monomers in step 3) are styrene and methacrylic acid, the volume ratio of styrene to methacrylic acid is 2:1; When the monomers in step 4) are styrene and methacrylic acid, the mass ratio of styrene to methacrylic acid is 4.3:2.
2.
9. A porous core-shell magnetic composite microsphere prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the porous core-shell magnetic composite microspheres according to claim 9 in any one of cross-linking and encapsulating immobilized enzymes, heavy metal ion adsorption, protein purification, cell separation and drug carriers.
